Anesthetic management of placenta accreta in a low-resource setting: a case series. Issue 4 (November 2015) - Muñoz, L.A.; Mendoza, G.J.; Gomez, M.; Reyes, L.E.; Arevalo, J.J.
Highlights This study retrospectively examined the management of placenta accreta in a low-resource setting. Uterine preservations strategies were not available. Hysterectomy required general anesthesia in half of the cases. Good maternal and neonatal outcomes were achieved but there was an increased risk of blood loss.